Applications of nonverbal communication - Claremont Symposium on Applied Social Psychology (2003); Riggio, Ronald E.; Feldman, Robert S. (Robert Stephen), 1947- (Mahwah, N.J. : L. Erlbaum Associates, Publishers, 2005)
The goal of this edited volume is to present the practical applications suggested by research in non-verbal communication, as well as to highlight the limitations-noting where we simply do not yet know enough to safely and fully inform practice.
[Pt.] 1. Health Applications. Nonverbal communication and health care / Leslie Martin and Howard S. Friedman -- Facial expression decoding deficits in clinical populations with interpersonal relationship dysfunctions / Pierre Philippot [and others] -- [pt.] 2. Applications to Law and Politics. Nonverbal communication in the courtroom and the "appearance" of justice / Michael Searcy, Steve Duck, and Peter Blank -- Police use of nonverbal behavior as indicators of deception / Aldert Vrij and Samantha Mann -- Nonverbal behavior and political leadership / Al Goethals -- [pt.] 3. Applications to Business and Education. Business applications of nonverbal communication / Ronald E. Riggio -- Working on a smile: responding to sexual provocation in the workplace / Julie A. Woodzicka and Marianne LaFrance -- No more teachers' dirty looks: effects of teacher nonverbal behavior on student outcomes / Monica Harris and Robert Rosenthal -- [pt.] 4. Social and Cultural Issues. Withdrawal in couple relationships: exploring the causes and consequences / Patricia Noller [and others] -- Emotional intelligence and deception detection: why most people can't "read" others, but a few can / Maureen O'Sullivan -- Culture and applied nonverbal communication / David Matsumoto and Seung Hee Yoo.
Papers from the 2003 Claremont Symposium on Applied Social Psychology.
Includes bibliographical references and indexes.
Print version record.
English.
Added to collection customer.56279.3
Keywords: Nonverbal communication -- Congresses; Communication non verbale -- Congrès.; LANGUAGE ARTS & DISCIPLINES -- Communication Studies; Nonverbal communication; Conference papers and proceedings